Nilai-Nilai Pendidikan Agama Islam Hadis Keempat Kitab Al -Arba’in An-Nawawiyyah Karya Syaikh An-Nawawi - Via Nailil Ngyah; Nurul Mubin; Ngatoillah Linnaja (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the content and substance of the Fourth Hadith in Al-Arba'in An-Nawawiyyah, explore the Islamic educational values contained within it, and examine its relevance to contemporary Islamic religious education. This research employs a qualitative approach using library research methods through an examination of primary and secondary literature related to the hadith and Islamic educational concepts. The data were analyzed using content analysis techniques to reveal both textual and contextual meanings.The findings show that the Fourth Hadith provides an explanation of the gradual process of human creation, the decree of divine destiny encompassing sustenance, lifespan, deeds, and a person’s final fate, as well as an emphasis on the importance of righteous actions in determining one’s end. The hadith encapsulates holistic educational values, including divine values such as belief in destiny, reliance on God (tawakkul), patience, and spiritual awareness; and humanistic values such as moral responsibility, self-control, self-awareness, and consistency in worship and good deeds. These values remain highly relevant for character building in modern learners, especially in facing moral, spiritual, and social challenges.Based on the results, it can be concluded that the Fourth Hadith of Al-Arba'in An-Nawawiyyah plays a significant role in strengthening contemporary Islamic education, particularly in shaping character grounded in sound creed, noble ethics, and strong mental resilience. The findings are expected to serve as a reference for educators, educational institutions, and society in developing more integrative and applicable educational practices.